Pengaruh domperidon terhadap produksi ASI pada ibu yang melahirkan bayi premature - Tengku Ellya Fazilla; Guslihan Dasa Tjipta; Emil Azlin; Pertin Sianturi (Fakultas Kedokteran USU, 2013)
Mother who gave birth to premature babies often have difficulty getting adequate milk production. Various attempts to increase milk production have been made, including pharmacological interventions. One of the drugs that can be used is domperidone. Domperidone is a peripheral dopamine receptor antagonist, works by blocking the inhibitory effects of dopamine-mediated prolactin secretion, thereby increasing milk production. Three randomized double-blind study showed that domperidon can increase milk production without causing any side effects to the mother and baby.Keywords : domperidone; premature; breastfed